2010
DOI: 10.1007/s10549-010-1043-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of screening and prevention strategies among BRCA1/2-affected mutation carriers

Abstract: Comparative effectiveness research has become an integral part of health care planning in most developed countries. In a simulated cohort of women, aged 30–65, who tested positive for BRCA1 or BRCA2 mutations, we compared outcomes of mammography with and without MRI, prophylactic oophorectomy with and without mastectomy, mastectomy alone, and chemoprevention. Methods: Using Treeage 9.02 software, we developed Markov models with 25,000 Monte Carlo simulations and conducted probabilistic sensitivity analysis. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 60 publications
3
92
2
3
Order By: Relevance
“…However, this population appeared to have high endocrine symptom scores and lower sexual functioning. This has also been more or less described in other publications [5,7,8,15,16].…”
Section: Discussionsupporting
confidence: 59%
“…However, this population appeared to have high endocrine symptom scores and lower sexual functioning. This has also been more or less described in other publications [5,7,8,15,16].…”
Section: Discussionsupporting
confidence: 59%
“…Several other modeling studies have also found that the effectiveness of screening using MRI is only slightly lower than the effectiveness of screening Table 3. The effects of various annual screen protocols on the number of screen-detected cancers and interval cancers and node positives, as would be detected in the studies, as well as the predicted mortality reduction and probability of breast cancer death using MRI and mammography (30)(31)(32), and that screening BRCA1/2 mutation carriers using MRI and mammography is cost-effective (20,(30)(31)(32)(33). However, these modeling studies did not make a distinction between BRCA1 and BRCA2.…”
Section: Discussionmentioning
confidence: 96%
“…29 MRI has also been shown to be cost-effective when added to mammography and physical examination in women at high risk. 5,32 Adding MRI to the breast cancer screening regimen has been under discussion and has been endorsed by the American Cancer Society in formal recommendations set forth in 2007 for patients with known hereditary cancer syndromes, in untested fi rst-degree relatives of identifi ed genetic mutation carriers, or in women who have an estimated lifetime risk of breast cancer of 20% or more, as determined by models largely dependent on family history. 33 But MRI has a downside-it is less specifi c than mammography.…”
Section: Radiographic Surveillancementioning
confidence: 99%